2020
DOI: 10.3390/chemosensors8030047
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Carbon Dots Derived from Volvariella volvacea Mushroom for a Highly Sensitive Detection of Fe3+ and Pb2+ Ions in Aqueous Solutions

Abstract: In this study, Volvariella volvacea (VV) mushroom was utilized as a green carbon precursor to synthesize carbon dots (CDs) and applied as a fluorescent (FL) sensor to detect Fe3+ and Pb2+ ions. The VV-CDs showed a high photostability and FL properties with a quantum yield of about 11.5%. The VV-CDs exhibited an excitation-dependent emission manner, with an optimum emission wavelength at 440 nm excited at 360 nm. The VV-CDs were evaluated and shown to be facile and effective FL sensors for detecting Pb2+ and Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…It was the complexation between CQDs and Fe 3+ that resulted in electrons transfer from the CQDs to Fe 3+ and a resultant static FL quenching of the CQDs [ 45 ]. The –COOH and –OH functional groups on the CQDs mainly contributed to interacting with Fe 3+ [ 46 ]. The LOD of the cyanobacteria CQDs to Fe 3+ was 0.6026 mg L −1 with a high regression coefficiency (R 2 ) of 0.999.…”
Section: Resultsmentioning
confidence: 99%
“…It was the complexation between CQDs and Fe 3+ that resulted in electrons transfer from the CQDs to Fe 3+ and a resultant static FL quenching of the CQDs [ 45 ]. The –COOH and –OH functional groups on the CQDs mainly contributed to interacting with Fe 3+ [ 46 ]. The LOD of the cyanobacteria CQDs to Fe 3+ was 0.6026 mg L −1 with a high regression coefficiency (R 2 ) of 0.999.…”
Section: Resultsmentioning
confidence: 99%
“…This observation elucidates a possible static quenching mechanism in sensing Pb(II) ions by SQDs. [56][57][58] Similarly, in the presence of Bi(III), the overall changes in the slower and faster decay constants exist but not progressively from the original values (Table S1, ESI †). But at some concentrations of Bi(III), especially at 125, 175, 200, and 250 mM, significant changes were observed at the average decay constant values, but not progressive.…”
Section: àmentioning
confidence: 93%
“…Due to the concerns about improving and protecting living organisms, more optical detection methods that utilize CDs as a sensing element have been developed to detect Fe 2+/3+ [ 13 , 22 , 38 , 40 , 72 , 78 , 87 , 124 , 135 , 142 , 151 , 159 , 166 , 169 , 219 , 226 ], Cu 2+ [ 53 , 66 , 97 , 141 , 227 , 239 ], Pb 2+ [ 65 , 87 , 181 , 240 ], Cr 6+/4+ [ 23 , 85 , 193 , 241 ], and Co 2+ [ 51 ]. For instance, Shamsipur et al (2018) prepared green-emitting CDs instead of common blue-emitting CDs for selective and sensitive detection of Fe 3+ [ 159 ].…”
Section: Application Of Cd-based Optical Sensor For Environmental Mon...mentioning
confidence: 99%
“…The conversion of fungi/bacteria species into a value-added product such as carbonaceous nanomaterials has contributed to the green and sustainable improvement. Algal blooms [83], yogurt [84], enokitake mushroom [85], microalgae biochar [86], mushroom [87], agarose waste [88], and Shewanella oneidensis [89] have been previously chosen as a carbon resource (Table 6). A study conducted by Pacquiao et al (2018) demonstrated the increment of quantum yield of 11% to 39% upon passivation with tetraethylenepentamine in the presence of 5% v/v sulfuric acid [85].…”
Section: Fungi/bacteria Speciesmentioning
confidence: 99%